1995
DOI: 10.1139/b95-155
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition of newly shed needle litter of Scots pine and some other pine species in a climatic transect. X Long-term decomposition in a Scots pine forest

Abstract: Significant differences in the chemical composition of falling needle litter were found among various pine species. A comparison between the needle litter of northern species (Scots pine and lodgepole pine) and that of 17 other, southern species combined showed that concentrations of N, P, Mg, K, and lignin were significantly lower in the northern group. In contrast, the Mn concentration was significantly higher in this northern group. Along a transect from the Barents Sea (69°45′N) to the Carpathian Mountains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 12 publications
2
24
0
1
Order By: Relevance
“…The different decomposition rates in boreal and mountain Mediterranean forest soils complicate the interpretation of this finding, but in general the nutrient supply has a lower impact than water supply in tree growth in the studied forest stands. Berg et al (1995) supported this idea because they found that the annual actual evapotranspiration was positively related with mineral (N, P, S and K) decomposition so that when the cycling rate was high (warm sites), an adequate supply and retention of water has the highest importance for tree growth.…”
Section: Discussionmentioning
confidence: 89%
“…The different decomposition rates in boreal and mountain Mediterranean forest soils complicate the interpretation of this finding, but in general the nutrient supply has a lower impact than water supply in tree growth in the studied forest stands. Berg et al (1995) supported this idea because they found that the annual actual evapotranspiration was positively related with mineral (N, P, S and K) decomposition so that when the cycling rate was high (warm sites), an adequate supply and retention of water has the highest importance for tree growth.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, Aerts (1997) reported that leaf-litter N concentration followed a positive nonlinear relationship with actual evapotranspiration (AET) with the data collected from temperate, Mediterranean and tropical (2009b) regions, but with mimimal samples from boreal regions. Berg et al (1995) established exponential functions (p < 0.001) between both N and P concentration and MAT and MAP for Scots pine foliar litter across a small transect of MAT from -1.7 to 10.5…”
Section: General Levels Of N P and N:p Ratio In Leaf-litter Of Woodymentioning
confidence: 92%
“…Based on Berg's et al (1995) data, Oleksyn et al (2003 showed that for Scots pine, leaf-litter N decreased with latitude across European continent.…”
Section: Global Patterns Of Variation In Leaf-litter N and P Concentrmentioning
confidence: 99%
See 1 more Smart Citation
“…3b). Between 47 and 55N needle P concentration averaged 1.5 mg g 1 and Berg et al 1995). In situ litter (c, d) N and P divided by green needle concentrations shown in Fig.…”
Section: Nre From Senescing Needles In a Common-garden Studymentioning
confidence: 94%